Everyman's Talmud : the major teachings of the rabbinic sages - Cohen, Abraham, 1887-1957 (New York : Schocken Books, 1949)
Summarizes the teachings found in the Talmud on ethics, religion, law, and folklore.
Ch. VI. Social Life. Sect. I. The Individual and the Community. Sect. II. Labour. Sect. III. Master and Workman. Sect. IV. Peace and Justice --
Includes bibliographical references and index.
Ch. VII. The Moral Life. Sect. I. Imitation of God. Sect. II. Brotherly Love. Sect. III. Humility. Sect. IV. Charity. Sect. V. Honesty. Sect. VI. Forgiveness. Sect. VII. Temperance. Sect. VIII. Duty to Animals --
Ch. VIII. The Physical Life. Sect. I. Care of the Body. Sect. II. Rules of Health. Sect. III. Dietetics. Sect. IV. Treatment of Disease --
Ch. IX. Folk-Lore. Sect. I. Demonology. Sect. II. The Evil Eye. Sect. III. Magic and Divination. Sect. IV. Dreams. Sect. V. Superstitions --
Ch. X. Jurisprudence. Sect. I. The Courts. Sect. II. Judges and Witnesses. Sect. III. The Trial. Sect. IV. Modes of Punishment. Sect. V. Torts. Sect. VI. Found Property. Sect. VII. Bailment. Sect. VIII. Tenancy. Sect. IX. Sale and Delivery. Sect. X. Prescriptive Right. Sect. XI. Inheritance --
Ch. XI. The Hereafter. Sect. I. The Messiah. Sect. II. Resurrection of the Dead. Sect. III. The World to Come. IV. The Last Judgment. Sect. V. Gehinnom. Sect. VI. Gan Eden.
Keywords: Talmud -- Theology; Jewish law